Monitoramento estratégico de políticas públicas: Requisitos tecnopolíticos, proposta metodológica e implicaç\~oes práticas para a alta administraç\~ao pública brasileira - José Celso Cardoso Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The strategic monitoring of public policies is both a great lack and a great need for high Brazilian public administration. Among other reasons for this paradox is discussed in the text issues alienation and resignation, both applied to the institutional context. Then the questioning of the proposed strategic monitoring, understood as a methodology that seeks to permanent and systemic way, diagnose and expose weaknesses in selected public policies aimed at expanding the capacity to implement and create inventory of knowledge is made policy. Then, we present the description of the organization and analysis platform, highlighting some of its main categories: organizational capabilities, institutional processes and the delivery of goods and services to society. Finally, we discuss the operationalization of strategic monitoring and its main impediments, such as the difficulty in obtaining information, the resistance of the bureaucracy to systematize and deepen knowledge on public policy, increasing the embarrassment by exposing the weaknesses and low interest information for decision-makers of the genre. With this final reflection is made on the main challenges of strategic monitoring and seek to define possible routes to solve them.
Keywords: H8; H80; 330; state; government planning; strategic monitoring; public policies; PPA 2016-2019; Brazil